Beyond efficacy: The full public health impact of vaccines. Issue 9 (24th February 2016) - Saadatian-Elahi, Mitra; Horstick, Olaf; Breiman, Robert F.; Gessner, Bradford D.; Gubler, Duane J.; Louis, Jacques; Parashar, Umesh D.; Tapia, Roberto; Picot, Valentina; Zinsou, Jean-Antoine; Nelson, Christopher B.
Abstract: There is an active discussion in the public health community on how to assess and incorporate, in addition to safety and measures of protective efficacy, the full public health value of preventive vaccines into the evidence-based decision-making process of vaccine licensure and recommendations for public health use. The conference "Beyond efficacy: the full public health impact of vaccines in addition to efficacy measures in trials" held in Annecy, France (June 22–24, 2015) has addressed this issue and provided recommendations on how to better capture the whole public health impact of vaccines. Using key examples, the expert group stressed that we are in the midst of a new paradigm in vaccine evaluation, where all aspects of public health value of vaccines beyond efficacy should be evaluated. To yield a wider scope of vaccine benefits, additional measures such as vaccine preventable disease incidence, overall efficacy and other outcomes such as under-five mortality or non-etiologically confirmed clinical syndromes should be assessed in addition to traditional efficacy or effectiveness measurements. Dynamic modelling and the use of probe studies should also be considered to provide additional insight to the full public health value of a vaccine. The use of burden reduction and conditional licensure of vaccines based on collection of outcome results should be considered by regulatory agencies.